Ciguatera - Jorge R. Rey (EDIS)
ENY-741, a 5-page illustrated fact sheet by Jorge R. Rey, describes this form of food poisoning caused by ingestion of saltwater fish and invertebrates that have accumulated in their tissues a certain amount of the toxins produced by dinoflagellates. Includes references. Published by the UF Department of Entomology and Nematology, October 2007.